Examining the Role of Women’s Empowerment in Contraceptive Use among Reproductive- Age Women in Bangladesh: Examining the Role of Women’s Empowerment in Contraceptive Use among Reproductive (Dhaka University Journal of Science, 2025)
This research investigates the interplay between women’s empowerment and current contraceptive practices among Bangladeshi women, taking into account various socio-economic and demographic factors. The study analyzes data of 18,987 women aged 15-49 from the Bangladesh Demographic and Health Survey (BDHS), 2022. Women’s empowerment is assessed through latent variables related to household decision-making and attitudes toward wife beating using principal component analysis. Chi-square tests and mixed-effect binary logistic regression are employed to scrutinize the unadjusted and adjusted associations. The findings reveal a positive association between women’s empowerment and contraceptive use, highlighting the role of gender equality in fostering communication on reproductive health decisions and improving access to family planning services. Women in the 25–35 and 35+ age groups, urban residents, educated, employed, and media exposed women exhibit higher odds of contraceptive use. The unexpected discovery that wealthier women are less likely to use contraceptives challenges prevailing norms, prompting further exploration. These findings suggest that empowering women can play a crucial role in enhancing reproductive autonomy and access to family planning services. To that end, policy interventions such as education and awareness campaigns, community-based family planning initiatives, mobile health (mHealth) tools, and legal reforms aimed at strengthening women’s rights are essential. Such interventions can bridge socio-economic disparities, foster informed decision-making, and improve reproductive health outcomes across Bangladesh.Dhaka Univ. J. Sci. 73(2): 161-169, 2025 (July)